Myxoid leiomyosarcoma-decoding the puzzle in the Pandora’s box-pre to post operative - Janani, Ponn M.; Natarajan, Usha; Veerappan, Venkatachalam; Tirukurungudi Nambi, Anirudhan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Myxoid leiomyosarcomas (MLMS) are a rare form of uterine cancer developed from the smooth muscles of the uterus. It is a very aggressive tumour and usually presents as abdomino pelvic mass. This is a case report of a 47-year-old parous, perimenopausal lady with huge abdominopelvic mass mimicking ovarian cancer preoperatively, but postoperatively turned out to be MLMS. It was a tumor of size 40×30×9 cm, weighing 12 kg. Histopathological examination revealed myometrial neoplasm composed of atypical spindle to stellate cells disposed as loose sheets within an abundant myxoid stroma. Immunohistochemically, SMA and Ki-67 were positive, which clinched the diagnosis. Postoperatively, chemotherapy was decided for the patient, and she is presently doing well after a year of surgery.